Road map for biofuels in Europe - Ohm, Anne (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
Declining oil reserves, difficulties of achieving CO2 emission reductions in the transport sector and agricultural considerations have led to increased attention for biofuels in the EU. The EU has therefore commissioned the project REFUEL to make an overview of the technical and economic possibilities for increasing the use of biofuels in EU 25+. REFUEL is a large EU research project designed to encourage a greater market penetration of biofuels. To help achieve this goal, it will develop a biofuels road map, consistent with EU biofuel policies and supported by stakeholders involved in the biofuels field. Starting early 2006, the project involves seven renowned partners and will take 24 months to complete. REFUEL is financed by the European Commission under the 'Intelligent Energy - Europe' programme. The road map will pave the way for an "ambitious, yet realistic" target share for biofuels in the fuel mix for EU transport in 2030, and propose policies to get there. The target share will be in the order of 25 % of the total transport fuel consumption. A least-cost biofuel mix meeting this target will be calculated based on identification of biofuels production chains, conversion technology, and biomass feedstock potentials and cost in the EU25+. The impact on the main drivers will be assessed: Reducing greenhouse gas emissions, increasing security of supply, and socio-economic impacts, especially in agriculture. Key stakeholders, their motives, the actions required from them, the barriers they will meet, the optimal timing of their actions will be identified and analysed, and policies needed to mobilise stakeholders, create incentives and reduce barriers will be formulated. The resulting road map will consist of a systematically described set of actions to be taken, coherent in task allocation and timing. This paper builds on the preliminary results from the REFUEL project, most importantly "A preliminary Road Map for Biofuels" (www.refuel.eu). The paper focuses primarily on the overall set-up of the project and the socio-economic analyses.